Up against caste : comparative study of Ambedkar and Periyar - "Chatterjee, Debi" (Jaipur, 2004)
"The struggle for social justice and human rights in India is inextricably linked to the question of caste and caste-based social structure which continue to be what Marx had termed "decisive impediments to India's progress". Struggles against caste and the caste system have a long history. In modern times, the contributions of B.R. Ambedkar and E.V. Ramasami (popularly known as Periyar) are particularly significant. Ambedkar, hailing from an untouchable caste background, was the pioneer in teaching the untouchables the art of using political weapons for the betterment of their conditions. Through his scholarly works and social and political struggles, Ambedkar challenged the Brahminical order of society and sought to uphold the basic human rights of the depressed classes. E.V. Ramasami's contributions were no less significant. The imprint of his struggles are to be found in the social and political spheres of the Tamil region in southern India. His challenge to Brahminism was sought to be posited through an alternative, democratic culture. It was the unique Self-Respect Movement. While the ideas and movements of both Ambedkar and Periyar have been separately studied by many scholars, there is a dearth of comparative material. It is this area of comparative study that this book primarily deals with. The book analyses the relevance of their struggles in the context of contemporary conditions, noting the diverse trends in the post-Ambedkar and post-Periyar dalit struggles."
Keywords: Dalit